2011
DOI: 10.1111/j.1600-0838.2010.01261.x
|View full text |Cite
|
Sign up to set email alerts
|

Is there an interaction between BDKRB2−9/+9 and GNB3 C825T polymorphisms and elite athletic performance?

Abstract: The -9 deletion allele in the -9/+9 BDKRB2 polymorphism was previously associated with improved endurance performance. We compared the frequency distribution of the BDKRB2 -9/+9 (rs5810761) polymorphism between athletes (n=155) of sports with different demands (endurance runners; n=74 vs. sprinters; n=81) as well as between athletes of different competitive levels (elite level; n=46 vs. national level; n=109). These results were compared to those of 240 non-athletic healthy individuals. We also tested the infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 18 publications
2
20
0
1
Order By: Relevance
“…In opposition to these findings, the study of Eynon et al [810] revealed no correlation between the C825T polymorphism in the gene GNB3 coding for the guanine nucleotide binding protein β-polypeptide 3 and the BDKRB2 -9/+9 polymorphism, despite the fact that the GNB3 C825T polymorphism was previously associated with elite athletic performance.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In opposition to these findings, the study of Eynon et al [810] revealed no correlation between the C825T polymorphism in the gene GNB3 coding for the guanine nucleotide binding protein β-polypeptide 3 and the BDKRB2 -9/+9 polymorphism, despite the fact that the GNB3 C825T polymorphism was previously associated with elite athletic performance.…”
Section: Discussionmentioning
confidence: 94%
“…The gene has been shown to be associated with higher skeletal muscle metabolic efficiency and with endurance athletic ability [24, 25, 29]. However, its role in determining individual capacity for physical performance has not been clearly established [10, 26]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is thus very likely that the combined influence of several genetic loci with a significant contribution, complex interaction of multiple genetic polymorphisms (with or without an individual contribution) and/or gene-environment interactions rather than an individual effect of a single polymorphic site have an influence on individual variation of human athletic performance [1921, 27]. To test the potential interaction of two polymorphisms that have been previously associated with elite athletic performance and their combined influence on athletic status of Israeli elite athletes, Eynon et al [6] investigated the common variation of 9bp-9/ + 9 (rs5810761) of the bradykinin receptor b2 gene ( BDKRB2 ) and the GNB3 C825T polymorphism. The authors, however, observed no association in relation to endurance performance.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, when divided into tertiles according to their finishing times, the À9/À9 genotype was only overrepresented in the fastest tertile. However, Eynon et al [61] found no significant differences in the frequencies of the À9 allele and À9/À9 genotype between 74 Israeli endurance athletes and 240 controls. The same negative results were obtained by Sawczuk et al [62] and Grenda et al [63] in two studies involving 334 endurance athletes from Russia and Poland.…”
Section: Bdkrb2 29 and Rs1799722 T Allelesmentioning
confidence: 96%